KEPUTUSAN PREFERENSI INVESTASI ASET RIIL DAN ASET FINANSIAL DENGAN MODEL MINIMAX REGRET - Didit Herlianto (University of Merdeka Malang, 2011)
Target of investment would be kept if determining investment decision was in a certain condition. However, tobe able to realize the target was not easy too. This matter was caused in determining preference of investorinvestment given on to condition of uncertainty. Uncertainty investment could relate to the natural situation(states of nature) or dicey future situation. Relating to the problem above, hence intention of this research wouldgive the solution how to determine the investment decision in an uncertain condition, real asset investmentinstrument (gold property) and financial asset (obligation and share). Method used in determining decisionof preference of investment instrument was the model of analyzing the decision of investment of minimumregret. Result of research indicated that the economic investment decision in an uncertain condition was mostprecise preference investment instrument in the form of gold asset. Decision making in the preference investmentprincipally was approach base, that investor would experience the loss if event happened to cause thechosen investment instrument alternative less than real return maximum. This matter could be seen if investordid not choose the gold in its investment decision hence opportunity loss would be bigger, that was opportunityof loss property 10,3045%, opportunity loss obligation 19,6387% and opportunity loss share (IHSG) 9,7103%.